Is ultrasound a useful tool for supporting lymphedema diagnosis or monitoring the effectiveness of complex decongestive therapy in patients with breast cancer-related lymphedema? (Annals of Medical Research, 2021)
Aim: To determine whether ultrasound is a useful tool for supporting the diagnosis of lymphedema and/or monitoring the effectiveness of complex decongestive therapy in patients with breast cancer-related lymphedema (BCRL).Materials and Methods: We studied both arms of 21 BCRL patients (one affected, one not-affected as a control). Patients underwent 30 sessions of complex decongestive therapy and bandaging (5 days/week, 45 min/day). The skin was marked at 0, 10, 20, and 35 cm between the volar wrist and acromioclavicular joint and between the dorsal wrist and posterolateral margin of the acromion before treatment and on the last day of treatment. Volume of the arm (Vtotal) was calculated by circumferential measurements with dermal and subcutaneous tissue thickness and compliance measurements. We summed thicknesses as “UStotal” and averaged compliances to determine “Compliance” values. The change of values on the affected side were compared to the unaffected side. We examined correlations between Vtotal, (standard method), UStotal, and Compliance.Results: Change of Vtotal (p = 0.004) and UStotal (p = 0.045) with treatment were different between the affected and unaffected arm. Compliance did not change in affected side with treatment. When the correlation between Vtotal, UStotal, and Compliance are performed, before treatment, after treatment, and the change with treatment values were correlated between Vtotal and UStotal (r = 0.626, 0.604, 0.459 respectively), no correlation was found between Vtotal and Compliance.Conclusion: In these patients, UStotal can be used to support the diagnosis of BCRL and/or monitor treatment in this population. UStotal/body mass index of ≥0.41 mm/kg/m2 can aid the diagnosis of BCRL with 81% sensitivity, 90.5% specificity, and 0.823 area under the curve (AUC). However, compliance does not seem an appropriate measurement for diagnosis and/or treatment monitoring.Keywords: Lymphedema; ultrasound; decongestive treatment; arm volume.